OPTIMALISASI PERAN INTERNATIONAL CRIMINAL COURT DAN APLIKASI AKSI KEMANUSIAAN SEBAGAI INISIASI PENYELESAIAN KASUS ETNIS ROHINGYA - Ayub Torry Satrio K (Jurnal Dinamika Hukum, 2014)
Rohingya is an ethnic in Myanmar which becomes victim of human rights violation by the un-recognition of the ethnic citizenship. They also undergo several treatments which lead to genocide trials. The government of Myanmar did not take any optimal action in order to bring this problem to an end. There are three action proposed in this writings to initiate a problem solving, i.e.: a case settlement with the act of International Criminal Court based on Rome Statute 1998; a humanitarian action as a step regarding the government failure in overcoming the humanitarian crisis on the ethnic of Rohingya; and an application of hu-man security concept in order to bring back the security of Rohingya people. Those actions can be carried out through the mechanism of international organization such as UN and its derivative bodies; or through the mechanism of regional bodies where Myanmar is one of the member, ASEAN. Keywords : Rohingya ethnic, International Criminal Court, Humanitarian Action